U-shaped planer UWB antenna with unsymmetrical feed - Alam, A. H. M. Zahirul; Islam, Md. Rafiqul; Khan, Sheroz (2011)
A simple planer rectangular UWB is designed and the frequency band is further enhanced by changing the fed position. The effect of U-shaped slot on the patch is studied for unsymmetrical fed antenna. The antenna offers more than 114% bandwidth when printed on a substrate of dielectric constant 4.4.